2018
DOI: 10.1177/1468087418817447
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure versus low-pressure exhaust gas recirculation in a Euro 6 diesel engine with lean-NOx trap: Effectiveness to reduce NOx emissions

Abstract: Exhaust gas recirculation can be achieved by means of two different routes: the high-pressure route (high-pressure exhaust gas recirculation), where exhaust gas is conducted from upstream of the turbine to downstream of the compressor, and the low-pressure one (low-pressure exhaust gas recirculation), where exhaust gas is recirculated from downstream of the turbine and of the aftertreatment system to upstream of the compressor. In this study, the effectiveness of both exhaust gas recirculation systems on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…A horrible wrong decision from a management and engineering point of view at a specific time and place has generated a worldwide butterfly effect in the automotive industry. However, making the problem a virtue, Dieselgate has forced new regulations to obtain much more efficient and cleaner ICEs [8][9][10][11].…”
Section: What Is the Problem With Ice (Internal Combustion Engines)?mentioning
confidence: 99%
“…A horrible wrong decision from a management and engineering point of view at a specific time and place has generated a worldwide butterfly effect in the automotive industry. However, making the problem a virtue, Dieselgate has forced new regulations to obtain much more efficient and cleaner ICEs [8][9][10][11].…”
Section: What Is the Problem With Ice (Internal Combustion Engines)?mentioning
confidence: 99%
“…a denotes the applied strain rate at the oxidizer side and it is related to the velocity gradient. Equations (6)- (8) are solved by means of the CHEM1D tool. The user specifies the boundary conditions, namely T u , T fuel , p, a, air and fuel composition.…”
Section: Fgm Tablementioning
confidence: 99%
“…17 The use of biofuels together with EGR can also be beneficial in reducing engine emissions further. 18 He et al 19 and Huang et al 6 concluded that adding alcohols to the fuel blend dilutes the aromatics content of the fuel which tends to decrease the soot precursors. Although using biodiesel and ethanol increases the NO x emissions due to higher in-cylinder temperatures, this can be mitigated using EGR.…”
Section: Introductionmentioning
confidence: 99%